Hydrogen storage on pristine and Li-decorated BC6N monolayer from first-principles insights. (4th March 2021) - Rahimi, Rezvan; Solimannejad, Mohammad
Abstract : In the study conducted in the present research hydrogen storage properties of pristine and Li-decorated BC6 N monolayer are considered by first-principles calculations. It is predicted that the double-sided Li-decorated monolayer of BC6 N will reach a suitable substrate that adsorbs up to eight molecules of H2 with hydrogen storage capacities of 12.60 wt% and adsorption energies within in the range of 0.23–0.29 eV. Hydrogen desorption from 2Li/BC6 N (8H2 ) system can occur at TD  = 297 K and P  = 1 atm which is at the ambient conditions. Potential usage of 2Li/BC6 N adsorptive medium for practical hydrogen storage purposes is concluded from the results of the present study. GRAPHICAL ABSTRACT: